Light‐Driven Micromotors: Light‐Driven Sandwich ZnO/TiO2/Pt Janus Micromotors: Schottky Barrier Suppression by Addition of TiO2 Atomic Interface Layers into ZnO/Pt Micromachines Leading to Enhanced Fuel‐Free Propulsion (Small Methods 11/2019). Issue 11 (12th November 2019) - Pourrahimi, Amir Masoud; Villa, Katherine; Sofer, Zdeněk; Pumera, Martin
Abstract : In article number 1900258 by Martin Pumera and co‐workers, new light‐driven ZnO/TiO2 /Pt Janus micromotors with atomically smooth interfaces that can move faster than conventional ZnO/Pt are presented. The new ZnO/TiO2 type II heterojunction interfaces are used for the first time in light‐driven micromotors to suppress the Schottky barrier, resulting in a highly efficient charge transfer/separation and faster speed for heavy carriers.